If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20y + 39 = 4y + 7 Reorder the terms: 39 + 20y = 4y + 7 Reorder the terms: 39 + 20y = 7 + 4y Solving 39 + 20y = 7 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 39 + 20y + -4y = 7 + 4y + -4y Combine like terms: 20y + -4y = 16y 39 + 16y = 7 + 4y + -4y Combine like terms: 4y + -4y = 0 39 + 16y = 7 + 0 39 + 16y = 7 Add '-39' to each side of the equation. 39 + -39 + 16y = 7 + -39 Combine like terms: 39 + -39 = 0 0 + 16y = 7 + -39 16y = 7 + -39 Combine like terms: 7 + -39 = -32 16y = -32 Divide each side by '16'. y = -2 Simplifying y = -2
| n+6=(3n-5+n+3)/2 | | 7z+2-3z=23-3z | | d=(r+10)t*r | | 84=(2+2w)w | | Y+3=-5(x-9) | | log(x-7)+log(x-5)=log(48) | | 5.7x+3=3.2x-2 | | -7xy(4x+y)= | | g=7gh | | Y+2(y-5)= | | -9-n*7=-23 | | 5-3t=3t-7 | | 6(t-4)+4t=5(2t+5)-11 | | 4x-1=2.5 | | -4(y-4y)+5=-2(4y-y)+1+17y | | 9v^2-21v+10=0 | | -7v+15=0 | | 20=7x+13 | | 0.95x+0.05(6-x)=0.10(21) | | (6x^2+x+7)-(2x^2-9)= | | (16x^2+25y^2)(4x+5y)(4x-5y)=0 | | 8b+7b= | | 5x+3(-7x-7)=-101 | | 8(2x-4)=2(8x+2) | | 5x-6y=11fory | | P(x)=64x-0.25x^2-(-0.003x^2+4.2x+1000) | | W(2+w)=w(10-w) | | 0=5y+21 | | f(x)=4xLn(7x)-4x | | 4v-2=17 | | p(x)=13x-0.002x^2-(-0.004x^2+9.2x+5000) | | 2v+11=19 |